Energy & security in the industrializing world - Thomas, Raju G. C.; Ramberg, Bennett (University Press of Kentucky, 1990)
Provides detailed analyses of the related concerns of energy needs, the economy, and national security for developing countries -- Argentina, Brazil, Cuba, India, Pakistan, South Africa, South Korea, and Taiwan. The essays serve to underline the dangerous problem of nuclear proliferation for several of these countries have uneasy relations with their neighbors. In their detailed reviews of these eight nations -- their plans and their capabilities -- the contributors have provided a valuable source for a neglected area of international affairs.